Impulsive dirac-delta forces in the rocking motion - Prieto, Francisco (2004)
In this work the classical theory of one block rocking motion is revisited. A Dirac-delta type interaction as impact mechanism is found to be an alternative for the traditional model. Numerical computations with this new formulation have shown that the agreement with the classical theory is excellent for the case of slender blocks and small displacements. Good agreement with experimental data has also been found for the case of arbitrary angles and slenderness. A probabilistic study of the variations in the coe cient of restitution due to the cyclic degradation at corners during seismic action is also performed. The approach presented in this paper opens new lines for further theoretical developments and computational applications.